Development of an Implementation Facilitation Strategy to Link Mental Health Screening and eHealth Intervention for Clients in Ryan White-Funded Clinics in Chicago - Stump, Tammy K; Ethier, Kristen; Hirschhorn, Lisa R; Dakin, Andrea; Bouacha, Nora; Freeman, Angela; Bannon, Jacqueline; Gómez, Walter; Moskowitz, Judith T; Bouris, Alida (Journal of acquired immune deficiency syndromes (1999), 2022)
To reduce the impact of depression on people living with HIV, we are implementing a clinic-based behavioral health screener and referral to Optimizing Resilience and Coping with HIV through Internet Delivery, an evidenced-based intervention. We used the Consolidated Framework for Implementation Research to identify contextual barriers and facilitators in advance of implementation. Sixteen Chicagoland area Ryan White Medical Case Management sites. We conducted a sequential mixed-methods study with medical case managers and supervisors. Participants completed an online survey assessing Consolidated Framework for Implementation Research domains, scored on a 1 (strongly disagree) to 5 (strongly agree) scale. Survey results informed a purposive sampling frame and interview protocol. Interviews were analyzed by rapid qualitative analysis. On average, survey respondents (n = 58) slightly agreed with positive views of team culture, learning climate, and implementation readiness (mean = 3.80-3.87). Potential barriers included intervention complexity (mean = 3.47), needed human resources (mean = 2.71-3.33), and only slight agreement with relative advantage over existing screening/referral systems (mean = 3.09-3.71). Qualitative results (n = 15) identified low advantage for clinics with robust behavioral health systems but strong advantage in clinics without these services. Respondents identified system-wide training and monitoring strategies to facilitate implementation. Ryan White Medical Case Management sites are a generally favorable context for the implementation of the interventions. As illustrated in an implementation research logic model, barriers will be addressed through deploying strategies proposed to impact clinic- and individual-level outcomes, including electronic prompts (reduce complexity), training on Optimizing Resilience and Coping with HIV through Internet Delivery as a complement to other behavioral health services (increase relative advantage), and feedback during implementation (strengthen rewards/incentives).